Nutritional Status and Symptoms in Preschool Children With Autism Spectrum Disorder: A Two-Center Comparative Study in Chongqing and Hainan Province, China - Zhu, Jiang; Guo, Min; Yang, Ting; Lai, Xi; Tang, Ting; Chen, Jie; Li, Ling; Li, Tingyu (Frontiers in Pediatrics, 2020)
Objective This study was designed to compare the nutritional status and symptom of preschool children with autism spectrum disorder (ASD) from two regions of China, and to analyze the correlation between nutritional status and autistic symptoms. Methods In this cross-sectional study, 738 ASD children and 302 typically developing children (TD) from were recruited from Chongqing and Hainan of China. Symptoms of the children with ASD were assessed with Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Social Responsiveness Scale (SRS). Neurodevelopment of children with ASD was evaluated with Gesell Developmental Scale (GDS). Nutritional status was assessed by means of anthropometric data, biochemical assessment of micronutrients, and providing questionnaire and food frequency questionnaire (FFQ) to parents. Results Compared ASD children between two regions, the mean CARS, SRS and ABC scores of ASD children in Chongqing were significantly higher than those in Hainan. ASD children in Chongqing consumed less whole grains, poultry meats, seafood, milk, and fruits than those in Hainan. The serum levels of Ferritin, vitamin B12 (VB12), vitamin A (VA) and vitamin D (VD) were lower in ASD children of Chongqing than those in Hainan, and ASD children in Chongqing had higher deficiency rates of Zinc, ferritin, VA and VD than those in Hainan. Compared ASD children with local TD children, the serum levels of folate, VB12, and VD were consistent lower in both regions. VA, VD and folate were negatively correlated with ASD symptoms. VD and Zinc were positively correlated with the GDS scores of autistic children. Conclusions There are regional differences in nutrition status of ASD children. Micronutrients levels were related to ASD symptoms and development of ASD children. Therefore, it is essential to formulate detailed nutritional evaluation and provide individualized nutrition interventions for ASD children from different background.